Questionnements sur la compréhension militantEs libertaires Queer et féministes au Québec à l'égard du Nous femmes et la non-mixité - Fortier, Ashley (Faut-il réfuter le Nous femmes pour être féministe au XXIe siècle?, 2009)
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; cours; débat; fem1000; féminisme libertaire; féminisme queer; histoire et politique; interdisciplinarité; militance; pratiques féministes; premier cycle; périodes historiques; queer; québec; ressource en ligne; régions géographiques; thématiques

The emotions least relevant to politics? Queering autonomous activism - Wilkinson, Eleanor (Emotion, Space and Society, 2009)
Studies of emotion and activism have often attempted to uncover ‘the emotions most relevant to politics’ (Goodwin et al., 2001). This suggests that only certain feelings are productive for activism, while other emotions have less relevance for activist theory and practice. In this paper I ask if the notion of politically ‘relevant’ emotions helps perpetuate a distinction between what is considered political and what is not. This paper builds upon a case study in which I interviewed self-identified queer-activists about their experiences of autonomous activism. These interviews reveal how the everyday emotions surrounding the ‘personal’ politics of sexuality/intimacy are often seen as either less important, a distraction from, or entirely irrelevant to ‘real’ political issues. Ultimately, I want to challenge attempts to neatly separate our intimate lives from the public sphere of activism. I argue that it can never just be a matter of politics and emotion, but also the politics of emotion (Ahmed, 2004). Therefore we should not just assume that emotions matter for resistance - without first realizing the importance of resisting these hierarchies of emotion.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; europe; militance; périodes historiques; queer; ressource en ligne; royaume-uni; régions géographiques; sexualité; thématiques; émotions; étude qualitative